“Being an Instance of the Norm”: Women, Surveillance and Guilt in Richard Yates’s Revolutionary Road - Vavotici Francesca (European Journal of American Studies)
This paper will analyze how space as both a physical environment and a social construct affects what Judith Butler calls ‘gender regulations’: how does the intersection of the private and the public influence the development of personal identity? How can these stereotypes be challenged within the confines of structured social and gendered hierarchies? The notion of suburbia as a physical representation of social anxieties and codified behaviours will firstly be introduced. In particular, the paper will look at how a male authoritarian rhetoric that sees happiness as a commodity rejects the idea of individual identity and serves to generate the conventional role of the all-American housewife as the only aspiration for female characters. Through an investigation into the development of different female characters, the paper will then highlight the ways in which adherence to the suburban social norm that regulates gender relationships leads to a renunciation of personhood in favour of conformity and designates the ostracisation of April Wheeler as an outcast. The semiotics of female identity that surrounds the character of April will be examined to show how this ostracisation is not only an external process of separation form society, but becomes an internalised action that leads to a fracture in the female consciousness that can only be overcome through the adoption of an alternative, extra-linguistic semiotics.